2008
DOI: 10.1002/mds.22293
|View full text |Cite
|
Sign up to set email alerts
|

Nordic walking improves mobility in Parkinson's disease

Abstract: Nordic walking may improve mobility in Parkinson's disease (PD). Here, we examined whether the beneficial effects persist after the training period. We included 19 PD patients [14 men; mean age 67.0 years (range 58-76); Hoehn and Yahr stage range 1-3] who received a 6-week Nordic walking exercise program. Outcome was assessed prior to training (T1), immediately after the training period (T2) and-in a subgroup of 9 patients--5 months after training (T3). At T2, we observed a significant improvement in timed 10-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
106
2
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 117 publications
(118 citation statements)
references
References 26 publications
3
106
2
7
Order By: Relevance
“…Table 1 summarizes the quality of the included studies. Three studies showed no random allocation 28,35,36 , and four studies showed no concealed allocation 28,29,35 . No study used blinded subjects and therapists, or showed an intention to treat.…”
Section: Literature Searchmentioning
confidence: 97%
See 4 more Smart Citations
“…Table 1 summarizes the quality of the included studies. Three studies showed no random allocation 28,35,36 , and four studies showed no concealed allocation 28,29,35 . No study used blinded subjects and therapists, or showed an intention to treat.…”
Section: Literature Searchmentioning
confidence: 97%
“…Total intervention sessions ranged from 24 36 to 72 31 , and the duration of each session varied from 60 27,28,35,36 to 70 31 minutes for a total of 6 28 to 24 31 weeks. Only two studies reported the intensity of Nordic walking 35,36 (moderate as evaluated by ratings of perceived exertion level, and high intensity measured by a heart rate monitor).…”
Section: Quality Assessmentmentioning
confidence: 99%
See 3 more Smart Citations